2016
DOI: 10.1016/j.msec.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the fracture toughness of hydroxyapatite (HAp) by incorporation of carboxyl functionalized single walled carbon nanotubes (CfSWCNTs) and nylon

Abstract: The potential of improving the fracture toughness of synthetic hydroxyapatite (HAp) by incorporating carboxyl functionalized single walled carbon nanotubes (CfSWCNTs) and polymerized ε-caprolactam (nylon) was studied. A series of HAp samples with CfSWCNTs concentrations varying from 0 to 1.5 wt.%, without, and with nylon addition was prepared. X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM) were used to characterize the samples. The three point bending te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…One of the interesting research areas in the field of block copolymers is synthesis of polymeric nanocomposite while one of the comonomers is a reactive nanoparticle [1,2]. Particularly, the use of polyhedral oligomeric silsesquioxanes (POSS) nanoparticle has been considered as an attractive and effective way in preparation of nanohybrids at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…One of the interesting research areas in the field of block copolymers is synthesis of polymeric nanocomposite while one of the comonomers is a reactive nanoparticle [1,2]. Particularly, the use of polyhedral oligomeric silsesquioxanes (POSS) nanoparticle has been considered as an attractive and effective way in preparation of nanohybrids at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…When the osteons alignment is parallel to the loading direction, crack grows under Mode I (Fig. 3(b) ) is in the range of the cortical bone fracture values [16]. Such a value is then compared with those determined by Libonati et al [13] according to ASTM standards [14] from C(T) type.…”
Section: Resultsmentioning
confidence: 99%
“…These modifications are brought about usually by surface functionalisation via acidification and oxidation or by using surfactants. As a result, through appropriate processing techniques, carbonaceous structures can mechanically strengthen a hydroxyapatite matrix via crack bridging and deflection mechanisms [ 6 , 57 , 72 ].…”
Section: Carbon and Its Structuresmentioning
confidence: 99%
“…Kalmodia et al [ 145 ] manufactured a HAp -Alumina (Al 2 O 3 ) -multiwalled carbon nanotubes (CNTs) composite. Previous, separate studies showed an enhancement of fracture toughness of the HAp matrix using individual Al 2 O 3 reinforcement [ 146 , 147 ] and CNT reinforcement [ 72 , 93 , 98 , 99 ]. In this study, researchers were interested in investigating the combined reinforcing effect of CNT and Al 2 O 3 in a HAp matrix.…”
Section: Other Systems Involving Carbon Structures and Hydroxyapatmentioning
confidence: 99%
See 1 more Smart Citation